Clinical Impact of a Pharmaceutical Care Programme Developed in a Family Health Unit: Results of a Pharmacist-Physician Collaboration in the Treatment of Hypertensive Patients - Mónica Condinho; Jorge Sá; Arquimínio Eliseu; Isabel Vitória Figueiredo; Carlos Sinogas (Formifarma, LDA., 2016)
Introduction: The positive impact of pharmacist-physician collaborative care has been reported in the international literature, although examples of this impact are limited in Portugal. We aim to underline the clinical added value for hypertensive patients that results from pharmacist-physician collaborations. Methods: A community trial was conducted at a Portuguese family health unit for 19 months. The intervention group was randomly selected from the global records and members of the group received pharmaceutical care in addition to physician care. The comparison group received only physician care. Both groups were comparable at the beginning of the study. In the intervention group, we analysed the hypertensive patients to evaluate the impact of pharmacist-physician collaboration on the patients' blood pressure levels. This evaluation was performed by comparing the obtained blood pressure levels with the levels at baseline and between the groups. Results: A total of 17 patients with hypertension were enrolled in the pharmaceutical care programme, 12 of whom were female. The mean age was 68.50±3.26 years and, on average, each patient consumed 6.06±0.93 medicinal products. Thirteen patients were uncontrolled. Compared with the baseline, the intervention group achieved mean reductions of 28.85±5.90 mmHg (p < 0.0005) and 11.23±2.75 mmHg (p < 0.005) in their systolic and diastolic blood pressure, respectively. Considering the comparison group, improvements of 18.63±6.44 mmHg (p = 0.011) in systolic blood pressure and 9.03±2.63 mmHg ( p < 0.005) in diastolic blood pressure were observed. Conclusion: Pharmacist-physician collaborative care adds clinical value to the typical physician care provided to hypertensive patients within the context of a Portuguese family health unit.